Behavioural determinants of ranchers towards sustainable edible-nest swiftlet ranching in Malaysia - K N Vaiappuri, Selvakkumar (2017)
The edible-nest swiftlet ranching is a unique industry in the agriculture sector in Malaysia, which also holds the same position in a global context. The edible-nest swiftlet ranching is an activity of which the edible-nest swiftlet birds are lured into a man-made building (bird house) which emulates a cave-like environment in order to provide alternative nesting sites to populate their colony. This edible bird nest (EBN) will be collected by a rancher after the young bird starts to fly. In the edible-nest swiftlet ranching, the birds will have the freedom to live in their natural “lifestyle” and will not be disturbed by the ranchers in any aspects. The development of the edible-nest swiftlet ranching in Malaysia has expanded rapidly when the Malaysian government gave special attention to the sector. However, this has led to an unplanned expansion among the ranchers which triggered several sustainability issues. If the sustainability issues are not handled well, the future of the sector will be at stake.